The sizzle and fizzle of teacher evaluation in the United States and the selective use of research evidence - Gitomer, Drew H.; Marshall, Brittany L. (Frontiers in Education, 2023)
In 2009, the United States funded the largest federal educational reform effort in the nation's history. Referred to as Race to the Top (RTTT), a cornerstone of this effort was the high-stakes evaluation of all teachers, with a significant emphasis on the use of highly researched statistical methods that ascribed changes in student test scores to a teacher's quality. The widespread endorsement of these policies across a broad range of the political spectrum was based on a theory of action that faced technical, organizational, and political challenges. Enthusiasm for these evaluation efforts was substantially muted in a mere five years. Among a number of factors, we argue that the framing of the problem together with privileging particular lines of research and voices, as well as the lack of consideration of other frames and attention to other research and voices, resulted in an evidence base that was wholly insufficient to justify the large-scale policy changes that were enacted.